INNOVATIVE APPROACHES TO TEACHING NATURAL SCIENCE IN CAMBODIAN PRIMARY EDUCATION - Maria Grace E. Lucas (SMART: Journal of Multidisciplinary Educational, 2025)
primary education, focusing on the integration of inquiry-based learning, technology-enhanced instruction, and culturally responsive pedagogy. The research employs a literature-based method, systematically reviewing peer-reviewed journal articles, conference papers, and institutional reports published within the last five years. Data were collected through structured searches using keywords such as “primary science education,” “innovative teaching,” “Cambodia,” “inquiry-based learning,” and “ICT in classrooms,” followed by thematic content analysis to identify patterns, gaps, and effective strategies. The findings indicate that inquiry-based activities and the use of digital tools enhance student engagement, conceptual understanding, and scientific literacy. Teacher preparedness, pedagogical content knowledge, school infrastructure, and contextual adaptation significantly mediate the successful implementation of these methods. The study identifies a research gap in applying these integrated approaches at the primary level in low-resource, culturally diverse contexts such as Cambodia, where challenges include limited materials, multi-grade classrooms, and insufficient ICT access. The novelty of this research lies in proposing a context-sensitive framework that combines technology, inquiry, and cultural responsiveness tailored to primary school settings, offering both theoretical contributions and practical guidance for policymakers, educators, and curriculum developers. Overall, the study concludes that sustainable improvements in primary science education require systemic coordination of pedagogy, technology, and cultural adaptation, providing a model applicable not only in Cambodia but also in similar global contexts. These insights contribute to the broader discourse on early science education innovation and strategies to enhance scientific literacy in low-resource environments.